Nitrogen balance and delta15N: why you're not what you eat during nutritional stress. - Fuller, Benjamin T; Fuller, James L; Sage, Nancy E; Harris, David A; O'Connell, Tamsin C; Hedges, Robert E M (Rapid Commun Mass Spectrom, 2005)
While past experiments on animals, birds, fish, and insects have shown changes in stable isotope ratios due to nutritional stress, there has been little research on this topic in humans. To address this issue, a small pilot study was conducted. Hair samples from eight pregnant women who experienced nutritional stress associated with the nausea and vomiting of morning sickness (hyperemesis gravidarum) were measured for carbon (delta13C) and nitrogen (delta15N) stable isotope ratios. The delta13C results showed no change during morning sickness or pregnancy when compared with pre-pregnancy values. In contrast, the delta15N values generally increased during periods of weight loss and/or restricted weight gain associated with morning sickness. With weight gain and recovery from nutritional stress, the hair delta15N values displayed a decreasing trend over the course of gestation towards birth. This study illustrates how delta15N values are not only affected by diet, but also by the nitrogen balance of an individual. Potential applications of this research include the development of diagnostic techniques for tracking eating disorders, disease states, and nitrogen balance in archaeological, medical, and forensic cases.
Keywords: Adult; Diet; Diet, Vegetarian; Feeding and Eating Disorders; Female; Hair; Humans; Morning Sickness; Nitrogen; Nitrogen isotopes; Pilot Projects; Pregnancy; Prenatal Nutritional Physiological Phenomena; Stress, Physiological; Weight Gain; Weight Loss